COMPORTAMENTO TÉRMICO DE EDIFICAÇÕES COM CAPTADORES DE VENTO MULTIDIRECIONAIS E COBERTURA VERDE - Andrade, Nixon; Dornelles, Kelen (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This research aims to evaluate the thermal behavior of a building with four types of wind tower, acting as catcher, associated with green roofs, using computational simulations with the EnergyPlus® software. The methodology of the work has the following steps: construction of the geometry of the models, definitions of the envelope, including the natural ventilation, and simulations in the EnergyPlus® software, for eight cities, representing each of the Brazilian bioclimatic zones, during the winter and summer periods. From the analysis of the results, represented by the graphs of the average day, it was observed that the green cover on the tower slab and / or the building reduced the internal air temperature in these environments, mainly in the Bioclimatic Zone 6, represented by the city of Goiânia , where there was a reduction of up to 6.4 ° C of the internal temperature of the building in relation to the external, directing architects and engineers to incorporate the wind towers correctly in their projects.